2012
DOI: 10.4161/auto.8.1.18274
|View full text |Cite|
|
Sign up to set email alerts
|

Induction of autophagy contributes to the neuroprotection of nicotinamide phosphoribosyltransferase in cerebral ischemia

Abstract: Recent reports indicate that autophagy serves as a stress response and may participate in the pathophysiology of cerebral ischemia. Nicotinamide phosphoribosyltransferase (Nampt, also known as visfatin), the rate-limiting enzyme in mammalian NAD + biosynthesis, protects against ischemic stroke through inhibiting neuronal apoptosis and necrosis. This study sought to determine the involvement of autophagy in neuroprotection of Nampt in cerebral ischemia. Middle cerebral artery occlusion (MCAO) in rats and oxygen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
243
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(262 citation statements)
references
References 45 publications
14
243
3
2
Order By: Relevance
“…However, the role of autophagy in ischaemic stroke is still controversial. Induction of autophagy by nicotinamide phosphoribosyltransferase increases the cell survival rate and simultaneously decreases the LDH leakage of primary neurons with 2‐hr OGD treatment 57. But other studies have reported that activation of autophagy can aggravate cortical neural cell injury following 1‐hr focal cerebral ischaemia/24‐hr R 58, 59.…”
Section: Discussionmentioning
confidence: 98%
“…However, the role of autophagy in ischaemic stroke is still controversial. Induction of autophagy by nicotinamide phosphoribosyltransferase increases the cell survival rate and simultaneously decreases the LDH leakage of primary neurons with 2‐hr OGD treatment 57. But other studies have reported that activation of autophagy can aggravate cortical neural cell injury following 1‐hr focal cerebral ischaemia/24‐hr R 58, 59.…”
Section: Discussionmentioning
confidence: 98%
“…Autophagy is an essential degraded process that removes the damaged organelles and toxic proteins and subsequently recycles amino acids to facilitate cellular energy production, limit endoplasmic reticulum stress, and promote cell survival under subsequent ischemic exposure 8, 51, 52. Although controversies remain about the role of autophagic activation in stressful conditions, a great deal of studies have demonstrated that induction of autophagy contributes to the neuroprotection in response to cerebral ischemia8, 10, 52 or focal brain damage 9. As an AMPK activator, metformin has been revealed to induce autophagy through an AMPK‐dependent manner in heart tissue, which subsequently provides protection in response to stress 31.…”
Section: Discussionmentioning
confidence: 99%
“…A large pool of evidence has demonstrated that autophagy activation is neuroprotective in ischemic stroke 8, 9, 10. Despite the growing attention on autophagy as a novel target for ischemic brain injury, studies on agents that modulate autophagy and could be used clinically are still limited.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of autophagic and lysosomal pathways has been implicated in neuronal injury in a rat model of permanent focal cerebral ischemia [11] . Furthermore, by regulating the TSC2-mTOR-S6K1 signaling pathway, autophagy is induced and further promotes neuronal survival during cerebral ischemia [20] .…”
Section: Introductionmentioning
confidence: 99%